Optimal Fleet Policy of Rental Vehicles with Relocation: A Simulation Study - John-Carlo Favier; Subhamoy Ganguly; Timofey Shalpegin (Journal of Advanced Transportation)
Popularity of one-way car rentals poses a challenge to rental car fleet management and brings to focus the importance of a strategic decision for rental car operators: whether to implement a single-fleet or a multifleet model. The single-fleet model allows movement of vehicles between regions, whereas the multifleet model does not. It is not obvious whether a single-fleet model is optimal due to its pooling effect, or a multifleet model due to shorter car relocation times. In practice, different rental car operators use different models. To answer this conundrum, we develop two simulation models and compare them in terms of fleet utilisation, branch service level, relocations, and operating profit. We have taken the New Zealand rental car industry as an example as the country consists of two well-defined regions: the North Island and the South Island. The results indicate that a multifleet model has a higher service level at key centres and higher utilisation. At the same time, the single-fleet model is relatively more profitable at the expense of a lower service level in key centres due to vehicles accumulating in the South Island due to a significant volume of one-way southbound travel. Overall, the implementation of either model should depend on the strategic goals of the rental car operator. Our work will be useful for practitioners considering whether or not to pool their fleet when allowing for one-way rentals with subsequent relocation.